Phase decomposition behavior and its effects on mechanical properties of TiNbTa0.5ZrAl0.5 refractory high entropy alloy. (10th March 2021) - Cao, Yuankui; Zhang, Weidong; Liu, Bin; Liu, Yong; Du, Meng; Fu, Ao
Highlights: Thermomechanical processing induces phase decomposition in TiNbTa0.5 ZrAl0.5 alloy. The phase decomposition behavior strongly depends on forging temperature. Phase decomposition affects precipitation and solid solution strengthening at 25℃. Phase decomposition decreases high temperature strength by grain boundary sliding. Abstract: The mechanical properties of refractory high entropy alloys (RHEAs) strongly depend on their phase structures. In this work, the phase stability of a BCC TiNbTa0.5 ZrAl0.5 refractory high entropy alloy subjected to thermomechanical processing was evaluated, and the effects of phase decomposition on room/high temperature mechanical properties were quantitatively studied. It was found that, the thermomechanical processing at 800 °C and 1200 °C leads to phase decomposition in the TiNbTa0.5 ZrAl0.5 alloy. The phase decomposition is caused by the rapid rising of free energy of the primary BCC phase. The effect of the precipitates on room temperature strength is determined by the competition between the increasing in precipitation strengthening and the decreasing in solid solution strengthening. But at high temperatures (800−1200 °C), the phase decomposition causes significant reduction in strength, mainly due to the grain boundary sliding and the decreasing in solid solution strengthening.